1976
DOI: 10.1002/j.1552-4604.1976.tb02406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Diphenhydramine HCI In Pediatric Sleep Disorders

Abstract: Fifty children with a variety of sleep disorders were studied in a placebo-controlled, double-blind clinical trial of diphenydramine elixir given in a dosage of 1.0 mg/kg at bedtime. Sleep records measuring latency time, number of awakenings, and duration of sleep were compiled by the patient's parent. A global assessment as to the severity of sleep disturbance and the therapeutic effect of the medication and placebo was made on a weekly basis. Diphenhydramine was significantly better than placebo in reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 2 publications
1
36
0
Order By: Relevance
“…The second study was a randomized, controlled trial of diphenhydramine for sleep among 50 children ranging in age from 23 months to 12 years given doses of 1 mg/kg diphenhydramine nightly at bedtime for 1 week. As reported in the previous section that described this same study, toxicity was noted in only one patient (age not reported) and the effect was noted only as "mild drowsiness" (assumed to be daytime drowsiness) (72).…”
Section: Diphenhydramine: Chronic Exposures In Patients 6 Years Of Agsupporting
confidence: 59%
See 1 more Smart Citation
“…The second study was a randomized, controlled trial of diphenhydramine for sleep among 50 children ranging in age from 23 months to 12 years given doses of 1 mg/kg diphenhydramine nightly at bedtime for 1 week. As reported in the previous section that described this same study, toxicity was noted in only one patient (age not reported) and the effect was noted only as "mild drowsiness" (assumed to be daytime drowsiness) (72).…”
Section: Diphenhydramine: Chronic Exposures In Patients 6 Years Of Agsupporting
confidence: 59%
“…There was one level 1b study in which 50 children ranging in age from 23 months to 12 years were given doses of 1 mg/kg nightly for sleep for 1 week. "Mild drowsiness" developed in only one patient (age unknown, assumed to be "daytime" drowsiness as the drug was being used for sleep but the effect was not described by author) (72).…”
Section: Diphenhydramine: Chronic Exposures In Children Less Than 6 Ymentioning
confidence: 99%
“…Saitou et al (10) also reported that H 1 -antagonists caused a reduction of sleep latency in rats, although the experiment time and conditions were quite different from those in our study. In insomniacs, it was demonstrated that diphenhydramine and chlorpheniramine decreased sleep latency and it has been widely used clinically (24,25). Therefore, it is reasonable to presume that cyproheptadine is also an effective sleep inducer in the treatment of insomnia, classified as difficulty in falling asleep, similar to diphenhydramine and chlorpheniramine.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 DPH is widely accepted as an effective sedative. 18,[22][23][24][25][26][27][28] This antihistamine was found to be significantly more sedating than PL in children with the common cold. 18 The current lack of clarity regarding symptomatic care in children with cough as a result of URIs has created an environment in which many pediatricians prescribe, 29 many Internet sites recommend, 30 and therefore many parents administer cough suppressants or antihistamines to relieve these symptoms.…”
mentioning
confidence: 99%